Seasonal Variation of the Effect of Extremely Diluted Agitated Gibberellic Acid (10e-30) on Wheat Stalk Growth: A Multiresearcher Study - Peter Christian Endler; Wolfgang Matzer; Christian Reich; Thomas Reischl; Anna Maria Hartmann; Karin Thieves; Andrea Pfleger; Jürgen Hofäcker; Harald Lothaller; Waltraud Scherer-Pongratz (The Scientific World Journal)
The influence of a homeopathic high dilution of gibberellic acid on wheat growth was studied at different seasons of the year. Seedlings were allowed to develop under standardized conditions for 7 days; plants were harvested and stalk lengths were measured. The data obtained confirm previous findings, that ultrahigh diluted potentized gibberellic acid affects stalk growth. Furthermore, the outcome of the study suggests that experiments utilizing the bioassay presented should best be performed in autumn season. In winter and spring, respectively, no reliable effects were found.